Kebijakan Zonasi PPDB terhadap Penurunan Jumlah Siswa yang Berpotensi Memengaruhi Proses Pembelajaran Biologi di SMA Swasta se- Kabupaten Purworejo - Fajar Adinugraha (Pro-Life, 2023)
This research article aims to determine the development of the number of private high school students before and after the PPDB zoning was implemented in Purworejo Regency. In addition, this article aims to implement Biology learning in private high schools. This research method was library research from the primary source of the Dapodik web for data on the number of students. In addition, the survey method with interview techniques was carried out as biological learning data. The number of private high school students has decreased since the PPDB zoning was implemented in Purworejo Regency. The potential loss of private high school students is estimated to be that they choose state high schools, state vocational schools, and private vocational schools and do not rule out religion-based schools (Ministry of Religion). Biology learning has been carried out well by the teacher. The small number of students also has an impact on motivation and the academic atmosphere at school. In addition, the constraints experienced in learning Biology are a matter of time and the condition of students' academic ability. The solution to overcome this problem is that the government needs to work together with private schools to reduce inequality in the number of students by revising the PPDB zoning policy, and schools need to carry out an appropriate school marketing strategy.